Evaluasi Kepuasaan Penggunaan Sistem Akademik Menggunakan Metode WebQual 4.0 dan IPA - Ari Hardiyantoro Susanto; Edi Surya Negara (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Musi Rawas University is one of the private tertiary institutions in the LLDIKTI Region II Sumbagsel area which is based in Lubuklinggau City, South Sumatra. Based on PDDIKTI data for the 2021/2022 academic year, Musi Rawas University has 11 Study Programs with a total of 1,706 students. Since the implementation of SIAKAD, Unmura has never evaluated both the quality aspect of its use and the performance of the system. This is of course important to do, because this SIAKAD will not only be applied in the present but will continue to be sustainable every year. In addition, the intended evaluation will have important value for management as an inside for the development and improvement of SIAKAD so that it can be better in the future. Performance evaluation of SIAKAD at Musi Rawas University. To do this, one of the analytical methods known as Webqual 4.0 and IPA (Importance Performance Analysis) will be applied. The results obtained from this study are the usability indicator of the correspondent's answer getting a satisfied response with a value of 75.4%, and the informant quality indicator of the correspondent's answer getting a satisfied response with a value of 77.4% and the interaction quality indicator of the correspondent's answer getting a satisfied response with a value of 63.4%.